2024
DOI: 10.1029/2023gh000997
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of the Respiratory Health Impacts of Wildfire Smoke PM2.5 in California

V. Do,
C. Chen,
T. Benmarhnia
et al.

Abstract: Wildfire smoke fine particles (PM2.5) are a growing public health threat as wildfire events become more common and intense under climate change, especially in the Western United States. Studies assessing the association between wildfire PM2.5 exposure and health typically summarize the effects over the study area. However, health responses to wildfire PM2.5 may vary spatially. We evaluated spatially‐varying respiratory acute care utilization risks associated with short‐term exposure to wildfire PM2.5 and explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…While McArdle et al [3] did not stratify by race/ethnicity, other recent studies reported stronger associations between wildfire smoke PM 2.5 and respiratory acute care utilization among certain groups. Duncan et al [5] reported stronger associations among Black/African American residents in western North Carolina, and Do et al [24] in California communities with higher percentages of Black or Pacific Islander residents. Effects on communities that have historically experienced disproportionate exposure to environmental hazards and related health impacts, including those who are Black/African American and Hispanic/Latino, should continue to be considered as climate change is projected to exacerbate existing inequities [25,26].…”
Section: Discussionmentioning
confidence: 98%
“…While McArdle et al [3] did not stratify by race/ethnicity, other recent studies reported stronger associations between wildfire smoke PM 2.5 and respiratory acute care utilization among certain groups. Duncan et al [5] reported stronger associations among Black/African American residents in western North Carolina, and Do et al [24] in California communities with higher percentages of Black or Pacific Islander residents. Effects on communities that have historically experienced disproportionate exposure to environmental hazards and related health impacts, including those who are Black/African American and Hispanic/Latino, should continue to be considered as climate change is projected to exacerbate existing inequities [25,26].…”
Section: Discussionmentioning
confidence: 98%